Terapia larval: protocolo básico de manutenção, desinfecção, transporte e aplicação de larvas de Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) - Gama, Renata A.; Brambilla, Paula B. T.; Silva, Sarah R. A.; Medeiros, Jucélia R.; Jales, Jéssica T.; Pinheiro, Marília A. R. Q.; Ferraz, Julianny B.; Motta Neto, Renato; Barbosa, Taciano M. (Entomological Communications, 2021)
Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) is an exotic blowfly in Brazil and it is considered one of the main species of medical-forensic importance. Their larvae have a necrophagous habit with a high forensic potential and they are also considered an important tool for treating chronic wounds, a technique known as maggot therapy, which is not yet routinely used in Brazil despite proven efficacy. In this context, the present work aims to describe a protocol for carrying out the technique, with the complete description of colony maintenance, preparation and disinfection of eggs, packing and transportation of larvae for use, application and removal of the larvae on patients. Thus, with this protocol, the maggot therapy can be disseminated and performed by other research groups.